Analysis of the Effect of Movement Due to the Relocation of the Mataram City Mayor's Office on Road Network Performance - Hidayat Jati Nasrullah Jati; Made Mahendra; Ida Ayu Oka Suwati Sideman (Green Publisher Indonesia, 2026)
This research was motivated by the planned relocation of the Mataram City Mayor's Office, which had the potential to alter traffic movement patterns and affect the performance of the surrounding road network. The rapid growth of urban activities has contributed to traffic congestion in the city center; therefore, the relocation of government offices was expected to support more balanced urban development while reducing traffic pressure. However, the relocation could also increase vehicle volumes on certain road segments and change the distribution of community travel patterns. This study aimed to analyze the magnitude of trip attraction and evaluate road network performance before and after the relocation of the mayor’s office. The study employed a quantitative approach using a four-step transportation planning model combined with road performance analysis based on the 2023 Indonesian Road Capacity Guidelines (Pedoman Kapasitas Jalan Indonesia / PKJI) and transportation simulation software. The results indicated an increase in traffic volume on several road segments leading to the new office location, which affected the decline in road service performance at certain points. Therefore, appropriate traffic management strategies and infrastructure improvements are required to maintain optimal road network performance.